2017
DOI: 10.3390/bioengineering4030070
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Glycoengineered RSV-F in the Human Artificial Lymph Node Reactor

Abstract: Subunit vaccines often require adjuvants to elicit sustained immune activity. Here, a method is described to evaluate the efficacy of single vaccine candidates in the preclinical stage based on cytokine and gene expression analysis. As a model, the recombinant human respiratory syncytial virus (RSV) fusion protein (RSV-F) was produced in CHO cells. For comparison, wild-type and glycoengineered, afucosylated RSV-F were established. Both glycoprotein vaccines were tested in a commercial Human Artificial Lymph No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…[43,44] With this eLN model, we sought to find a hydrogel blend formulation capable of supporting cellular characteristics and providing mechanical stability to sustain the embedded channel lumen. In contrast to other studies using collagen or agarose hydrogels as a scaffold, [39,45,46] we observed that collagen-based gels rapidly contracted and were unable to maintain a perfusable channel. This was likely due to the presence of multiple cell types at a high density, including fibroblasts.…”
Section: Discussioncontrasting
confidence: 99%
“…[43,44] With this eLN model, we sought to find a hydrogel blend formulation capable of supporting cellular characteristics and providing mechanical stability to sustain the embedded channel lumen. In contrast to other studies using collagen or agarose hydrogels as a scaffold, [39,45,46] we observed that collagen-based gels rapidly contracted and were unable to maintain a perfusable channel. This was likely due to the presence of multiple cell types at a high density, including fibroblasts.…”
Section: Discussioncontrasting
confidence: 99%
“…This platform successfully recapitulated immune response profiles of humans, such as immunoreactions against different antigens. Similarly, Radke et al tested vaccine candidates in vitro using the commercial Human Artificial Lymph Node (HuALN) platform . The vaccine candidates of wild-type and glycoengineered afucosylated RSV-F (the recombinant human respiratory syncytial virus fusion protein) were analyzed in this device, indicating that this method was suitable for distinguishing the efficacy of two vaccine candidates with slight structural variations.…”
Section: Microfluidics For Drug Evaluationmentioning
confidence: 99%
“…For example, cell lines can't be used to fully replicate humoral immunity in which naïve B cells need to proliferate, differentiate and become antibody secreting cells. These limitations can be circumvented by the use of primary immune cells commonly purified from human blood and also tissue slices from human lymph nodes (Lin and Butcher, 2006;Higbee et al, 2009;Giese et al, 2010;Dauner et al, 2017;Radke et al, 2017;Goyal et al, 2019;Kraus et al, 2019). These attractive models, which, in fact, are still under development, attempt to be closer to the physiological behavior of the human lymph node.…”
Section: Technologies For Generating Lymph Nodes-on-chipmentioning
confidence: 99%
“…The HuALN ® enables long term culture of cells embedded in agarose matrix and the establishment of well-defined gradients. Authors showed this model is beneficial to study immune reactions and drug responses because they were able to detect micro-organoid structures (by histology and in situ imaging), to analyze genetic profiles and, to quantify cytokine and immunoglobulin secretion in the collected cell culture medium (Giese et al, 2010;Radke et al, 2017;Kraus et al, 2019)This model has been used to test glycoprotein vaccines and to study the immunogenicity of protein aggregates of two antibodies, bevacizumab and adalimumab, exposed at different stress conditions (Radke et al, 2017;Kraus et al, 2019).…”
Section: Bioreactor Human Artificial Lymph Nodementioning
confidence: 99%